Otomatisasi Sistem Pengereman pada Mobil menggunakan Sensor Jarak - Rodi Hartono; Fajar Petrus Apris Samosir; Okta Rusdiansyah; Rizky Naufal M (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
The factor of driver error in driving (human error) is one of the causes of the high number of traffic accidents in the present. To anticipate this, the discipline and concentration of the driver when driving is needed. However, when drivers have discipline and sufficient concentration of accidents can still occur. Therefore, the quality of the vehicle security system also greatly affects safety when driving. With the development of science and technology today it is very possible for humans to make security systems in vehicles. Accidents are often caused by the driver being unable to react quickly when there is a sudden blocking of objects. Especially when the driver is driving at high speed. This can be overcome by automating the braking system, so that the vehicle's speed will slow down even though the driver does not step on the brake lever. So that the possibility of an accident can be avoided. And automation is expected to be implemented in vehicles widely. In this study, designed a brake automation system using fuzzy logic by making a prototype. This prototype serves as a visual aid to evaluate the workings of the membership functions that will be used. From this evaluation it is known the value of each membership function. These values ​​are used as the main parameters in determining the Rules that will affect the output value of the brake force. With these Rules, automation of the brake system can work optimally. And it is known that the distance of the prototype car can run between other obstacle with a width of 50cm and the braking of the prototype car stops completely when the prototype is ± 5-10 cm with the obstacle in front of it. Keywords: Automation of Brake Systems, Fuzzy Logic, Distance, Speed.